PARADOKS BADAI PHK STARTUP: MENCAPAI SUSTAINABILITY DENGAN PENERAPAN AKUNTANSI MANAJEMEN - Andi Irfan; Dessyka Febria; Rinda Fithriyana (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2023)
The potential for startups to grow is not in line with the success of the startup itself. Finance is one of the problems that causes startup failure. This article examines how efforts to achieve sustainability by applying management accounting to find solutions to startup layoffs. The method used is literature study through review of research results, scientific references, online and offline literature. The result of this article is that startups can consider using an Activity Based Budgeting (ABB) approach to be able to prepare better budgets going forward. one of the causes of failure is the mismatch between the products being developed and market needs, so the application of benchmarking can be considered to rise and develop the business. Using ERP software, startups can create efficiency in work and excel in service so that business goals are achieved.